Effect of pivotal response training for children with autism spectrum disorder： a systematic review - Niluopa; Ailipati Tailaiti; Wang Minnan; Rena Maimaiti (Sichuan jingshen weisheng, 2024)
The purpose of this article is to systematically review the effectiveness of pivotal response training （PRT） for children with autism spectrum disorder （ASD）， so as to provide evidence-based guidance for the implementation of effective PRT for children with ASD. Randomized controlled trials （RCTs） investigating the effectiveness of PRT for children with ASD were collected， and the methodological quality of the trails was evaluated using the Cochrane Collaboration's tool for risk of bias assessment. A total of 6 RCTs were included in this review. Then the empirical findings including the implementation of PRT and the role of PRT in improving general social skills and verbal communication skills of children with ASD were elaborated. And its limitations and possible future research directions were also summarized. ［Funded by Special Project for Construction of Innovation Environment in Autonomous Region： Construction of Science and Technology Innovation Base （number， PT2306）］